Collision-Induced Infrared Absorption by Molecular Hydrogen Pairs at Thousands of Kelvin. (9th September 2009) - Li, Xiaoping; Hunt, Katharine L. C.; Wang, Fei; Abel, Martin; Frommhold, Lothar
Abstract : Collision-induced absorption by hydrogen and helium in the stellar atmospheres of cool white dwarfs causes the emission spectra to differ significantly from the expected blackbody spectra of the cores. For detailed modeling of radiative processes at temperatures up to 7000 K, the existingH 2 – H 2 induced dipole and potential energy surfaces of high quality must be supplemented by calculations with theH 2 bonds stretched or compressed far from the equilibrium length. In this work, we describe new dipole and energy surfaces, based on more than 20  000 ab initio calculations forH 2 – H 2 . Our results agree well with previous ab initio work (where those data exist); the calculated rototranslational absorption spectrum at 297.5 K matches experiment similarly well. We further report the calculated absorption spectra ofH 2 – H 2 for frequencies from the far infrared to 20 2009;000cm − 1, at temperatures of 600 K, 1000 K, and 2000 K, for which there are no experimental data.